Improving Students Activity and Students Mathematic Learning Outcomes by Using Two Stay Two Stray Model - Mahrudi Mahrudi; Abd Rahman (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2017)
The purpose of the research to improve students activity by using cooperative learning model with Two Stay Two Stray type. To improve students learning outcomes by using cooperative learning model with Two Stay Two Stray type.  The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIII at MTs.Bustanul Faizin With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is improving students activity and student learning outcomes.Keywords: Two Stay Two Stray, students activity, and students learning outcomes